'Preaching from the pews': A case study in vulnerable theological leadership - Ian A. Nell (Verbum et Ecclesia, 2015)
When explaining vulnerability as a theme for the conference of the Societas Homiletica, the organisers referred to two ways in which the concept can be interpreted. On the one hand, it can refer to preachers themselves as vulnerable people, subjected and accountable to other people. On the other hand, it can refer to the fact that preachers are often called to preach about difficult and challenging aspects of life and faith. In this sense, preachers speak on behalf of those who are vulnerable and in need of attention. In this contribution, both understandings are at play when the researcher takes a closer look at the sermons that were preached as part of a project known as the The sermon of the layperson in Stellenbosch, South Africa, during September and October 2013. An analysis of the contents of these sermons, as an exercise in preaching from the pews, shows that they were preached on behalf of vulnerable people. In the process of analysis, it also became apparent that the preachers were themselves examples of vulnerable theological leadership in the sense that they were lay people and therefore not in positions of official authority within faith communities. All of the preachers were however quite influential in their own areas of specialisation and professional life, and therefore, their sermons also communicated hope amidst situations of vulnerability.